2017
DOI: 10.1007/s11011-017-0147-5
|View full text |Cite
|
Sign up to set email alerts
|

Trigonelline insulates against oxidative stress, proinflammatory cytokines and restores BDNF levels in lipopolysaccharide induced cognitive impairment in adult mice

Abstract: Neuroinflammation is said to play a pivotal role in the pathogenesis of neurodegenerative disorders such as Alzheimer's disease (AD). Trigonelline (TRG) is a naturally occurring alkaloid, commonly isolated from fenugreek and coffee beans. In the present study, we investigated whether TRG exerts neuroprotective action against LPS mediated cognitive impairment. Mice pretreated with TRG (50 and 100 mg/kg po) were administered with LPS (250 μg/kg ip) for 7 days. Memory was assessed in the Morris water maze (MWM) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 60 publications
0
29
0
Order By: Relevance
“…Literature searching showed that the TRG has various pharmacological effects including hypoglycemic, hypolipidemic, neuroprotective, antimigraine, sedative, and memory-improving activities [24,[58][59][60]. Recently, it has been determined that TRG through the attenuation of oxidative stress and mitigation of neuroinflammation exerted a neuroprotective effect against LPS-mediated cognitive impairment [27]. We showed that the administration of TRG significantly reversed depressive-and anxiety-like behaviors of MS. We observed that TRG significantly decreased immobility time in the FST, increased grooming activity time in the splash test, and increased both open arm time and open time entries in the EPM of the MS mice.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Literature searching showed that the TRG has various pharmacological effects including hypoglycemic, hypolipidemic, neuroprotective, antimigraine, sedative, and memory-improving activities [24,[58][59][60]. Recently, it has been determined that TRG through the attenuation of oxidative stress and mitigation of neuroinflammation exerted a neuroprotective effect against LPS-mediated cognitive impairment [27]. We showed that the administration of TRG significantly reversed depressive-and anxiety-like behaviors of MS. We observed that TRG significantly decreased immobility time in the FST, increased grooming activity time in the splash test, and increased both open arm time and open time entries in the EPM of the MS mice.…”
Section: Discussionmentioning
confidence: 84%
“…TRG is a pyridine alkaloid isolated from coffee beans, fenugreek seeds, and so on, [55]. TRG exerted a neuroprotective action in a rodent model of Parkinson's disease [56] and also reversed cognitive impairment in mice model of Alzheimer's disease [27]. Tohda et al [57], reported that TRG stimulates functional neurite outgrowth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the present study suggested that trigonelline significantly reduced BUN, creatinine and albumin levels, indicating reduced inflammation in T2DM rats. Furthermore, Chowdhury et al (15) demonstrated that trigonelline protects against oxidative stress and proinflammatory cytokines in lipopolysaccharide-induced cognitive impairment in adult mice.…”
Section: Discussionmentioning
confidence: 99%
“…on mesenchymal stem cells to assess morphological changes that occur in response to the differentiation induction. Trigonelline has been known to exhibit medicinal properties like inhibition of adipocyte differentiation 9 , anticarcinogenic 10,11,12 , anti-hypercholesterolemia 13 , anti-diabetic and hypoglycemic 13,14,15 , antioxidant 10,16 , anti-apoptotic 17 activities and may help to prevent or at least increase the age when one suffers from obesity and associated effects.…”
mentioning
confidence: 99%